Endoscopic resection of colloid cyst: long-term followup with 65 patients. (3rd June 2015) - Hamilton, MG; Isaacs, A; Urbaneja, G; Hader, W; Yong, H
Abstract : Introduction: Colloid cysts of the third ventricle are rare, histologically benign lesions that can be associated with obstructive hydrocephalus. Endoscopic removal developed as an alternative to microsurgical craniotomy as a less invasive surgical treatment. This review examines the endoscopic surgical experience for a consecutive series of patients with colloid cyst of the third ventricle. Methods: Patients with a diagnosis of "colloid cyst of the third ventricle" who were treated in Calgary between January 1994 and July 2014 were reviewed using a clinic database and registry. Results: 95 patients were identified. 30 patients without hydrocephalus underwent serial MRI and clinical observation with one patient developing hydrocephalus leading to surgical treatment. 65 patients underwent endoscopic treatment of their colloid cyst (male=34; female=31). The mean age at diagnosis was 45.5 years. 3 patients had been previously treated with other surgical approaches. All surgically treated patients had hydrocephalus and hydrocephalus resolved in all 65 patients. 1 patient sustained an injury to the internal capsule with transient hemiparesis. Mean followup was 8.2 years (range 0.1-19.3 years). 3 patients experienced colloid cyst recurrence treated with a second endoscopic removal. Conclusion: Endoscopic treatment of third ventricle colloid cysts can be performed with low risk as an alternative to microsurgical resection.